Superorganism Immunity: A Major Transition in Immune System Evolution - Pull, Christopher D.; McMahon, Dino P. (Frontiers in Ecology and Evolution, 2020)
Social insect colonies can express adaptive, organism-like design. In some cases, colonies so resemble a unique, cohesive and integrated “individual” that they are termed superorganisms. The major evolutionary transitions framework explains, via inclusive fitness theory, how new levels of biological individuality, including genes into genomes within cells, cells into multicellular organisms and organisms into superorganisms can emerge. Importantly, it highlights how at each major transition similar challenges arose and why seemingly convergent solutions evolved. One challenge faced at each transition is exploitation, caused internally by social cheaters, and externally by parasites and pathogens. To overcome the problem of exploitation transitions in biological individuality required novel immune systems to maintain the integrity of newly emerged individuals. Multicellular organisms evolved an immune system while social insect colonies evolved a social immune system. In this review, we take a major transitions perspective of immunity to highlight the interdependency between the evolution of immune systems and the emergence of biological individuality. We build on the notion that superorganisms have evolved an immune system to promote the fitness of the colony. We draw parallels between the evolution of the metazoan immune system and the social immune system, and their expression as cognitive networks. Moreover, we discuss how research on other group-living species, such as family-based cooperative breeders, can inform our understanding of how social immune systems evolve. We conclude that “superorganism immunity” is an adaptive suite of organismal traits that evolves to maximise the fitness of advanced social insect colonies, fulfilling the same function as the immune system of Metazoa.